Konsep Asas No Work No Pay Terhadap Pekerja Oleh Perusahaan Terdampak Pandemi Covid-19 - Irfan, Muhammad; Subekti, Rahayu; Sungkowo Raharjo, Purwono (Jurnal Komunikasi Hukum, 2021)
This study aims to determine the concept of the no work no pay principle in laws and regulations by companies with the Covid- 19 Pandemic concept. Methods This research is a prescriptive normative legal research. The legal sources of this legal research use primary and secondary legal materials. The approach technique used is the method of applying the law and the conceptual approach. Data collection techniques used are literature study, document study and interviews. The technique of analyzing legal materials is descriptive using the deductive reasoning method. Results Based on research on the concept of wages according to the no work no pay principle by the Covid- 19 pandemic company, there are several concepts that can be used as guidelines. First, the basic concept refers to and is guided by the no work no pay principle contained in Article 93 paragraph (1) of Law Number 13 of 2003 concerning Manpower which reads "Wages are not paid if the worker/labourer does not do work" . The no work no pay principle applies if the Worker/Labourer does not work on the basis of the Worker/Labourer's own fault or intention. Because there is no work without wages, it does not apply if the condition of the Worker/Labourer experiences several conditions as regulated in Article 93 paragraph (2) of the Manpower Act. However, what is noted in the wage policy in the Covid-19 pandemic is that the provisions in Article 93 paragraph (2) letter f do not apply, because it cannot be fulfilled "the employer does not employ workers or laborers due to their own mistakes or because of obstacles that can be avoided by the entrepreneur" because the Covid-19 pandemic condition is an event that cannot be avoided and is not the fault of any party.